Primary inoculum of Venturia inaequalis (Cooke) Wint. in its asexual form in apple – a review - Rancāne, Regīna; Valiuškaitė, Alma; Stensvand, Arne (Frontiers in Horticulture, 2023)
This review summarizes and discusses geographical distribution, overwintering, dissemination, and management of the asexual stage of Venturia inaequalis, the fungal pathogen causing apple scab. Asexual overwintering of V. inaequalis has primarily been described as wood scab, superficial scab, or bud scab, and more rarely it is mentioned as overwintering on infected leaves and fruit still attached to the trees. Wood scab is fungal pustules found on new and 1-year-old shoots, but it is also described from 2-year-old wood. It has been reported from many apple growing countries throughout the world; however, most reports of wood scab being an important source of primary inoculum, as well as the most in-depth studies, are from the UK. Reports from some countries describe what is named superficial scab, which is symptomless infections of the pathogen on shoot surfaces. Overwintering of V. inaequalis on inner or outer bud scales has also been reported from some countries. Infections may appear as small lesions on the bud scales, but numerous conidia have also been found in buds without symptomatic fungal tissue. The incidence and quantity of overwintering in the asexual stage is dependent on the amount of scab in the previous season, growth characteristics and cultivar susceptibility of the shoots. In orchards with limited options for fungicide control and/or in orchards with loss of scab control in the preceding season, early release of conidia of V. inaequalis should not be underestimated as primary inoculum.